EVALUASI KUALITAS INFORMASI SITUS WEB PEMERINTAH DAERAH KABUPATEN TOLIKARA - Yeur Yikwa; Melkior Sitokdana (Jurusan Teknik Informatika, 2020)
AbstractInformation quality is one of the main indicators of successful application of information systems. System quality and information quality are both of the main factors determining user satisfaction and the success of an information system. This means that the quality of information determines public satisfaction and the successful implementation of e-Government in a government environment. Tolikara district in Papua province has had a website for a long time, but based on observations, various weaknesses are found in the quality of information. Therefore, in this study using descriptive qualitative methods and using 20 variables to measure the quality of website information, namely Accuracy, Consistency, Security, Timeliness, Completeness, Concise, Reliability, Accessibility, Objectivity, Relevancy, Useability, Understandability, Amount. of data Believability, Navigation, Reputation, Useful, Efficiency and Value-Added. Based on the analysis, it is found that there are several weaknesses or shortcomings, namely that some important data and information about the regions are not yet available on the Website, some menus and sub menus are not yet functioning properly and the existence of the Website is not quite useful for the public. Therefore, the recommendation is to improve the quality of information as a whole so that the existence of the website can provide benefits to the public and also facilitate the tasks of the Tolikara Regency Government.Keywords : Information Quality, e-Government, Website, Tolikara1. PENDAHULUAN Kualitas Informasi merupakan salah satu indikator utama keberhasilan penerapan sistem informasi.Kualitas sistem dan kualitas informasi adalah keduanya faktor utama yang menentukan kepuasan pengguna dan keberhasilan sistem informasi. Artinya bahwa kualitas informasi yang menentukan kepuasan publik dan keberhasilan implementasi e-Government dalam lingkungan Pemerintahan.Kabupaten Tolikara di Provinsi Papua sudah memiliki Situs Web sejak lama tetapi berdasarkan pengamatan ditemukan berbagai kelemahan dalam hal kualitas informasi. Oleh karena itu, dalam penelitian ini menggunakan metode kualitatif deskriptif dan menggunakan 20 variable untuk mengukur kualitas informasi Situs Web, yaitu yaitu Accuracy, Consistency, Security, Timeliness, Completeness,Concise, Reliability, Accessibility Availability, Objectivity, Relevancy, Useability, Understandability, Amount of data Believability, Navigation, Reputation, Useful, Efficiency dan Value-Added. Berdasarkan analisis ditemukan bahwa terdapat beberapa kelemahan atau kekurangan, yaitu sebagian data dan informasi penting tentang daerah belum tersedia di Situs Web, beberapa menu dan sub menu belum berfungsi dengan baik dan keberadaan Situs Web belum cukup berguna bagi publik. Oleh karena itu,rekomendasinya adalah perbaikan kualitas informasi secara menyeluruh agar keberadaan Situs Web tersebut dapat memberikan manfaat bagi publik dan juga memudahkan tugas-tugas Pemerintah Daerah Kabupaten Tolikara. Kata Kunci : Kualitas Informasi, e-Government, Situs Web, Tolikara